2022
DOI: 10.5267/j.dsl.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting model of COVID-19 pandemic in Malaysia: An application of time series approach using neural network

Abstract: COVID-19 has spread to more than a hundred countries worldwide since the first case reported in late 2019 in Wuhan, China. As one of the countries affected by the spread of COVID-19 cases, the local government of Malaysia has issued several policies to reduce the spread of this outbreak. One of the measures taken by the Malaysian government, namely the Movement Control Order, has been carried out since March 18, 2020. In order to provide precise information to the government so that it can take the appropriate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Within the scope of this study, many studies have been carried out in order to obtain predictions about the course of the pandemic through various time series models. In accordance with this purpose Turkey (Karcıoğlu et al, 2021;Akay & Akay, 2021;Fidan & Yuksel, 2022), Greece (Katris, 2021), Portugal (De Oliveira, et al, 2021, Italia (Ding et al, 2020;Ceylan, 2020;Dehesh et al, 2020), Worldwide (Sevli & Gülsoy;, Maleki et al, 2020, Petropoulos et al, 2022, USA (De Oliveira, et al, 2021;Özen et al, 2021;Shastri et al, 2020;Zeroual et al, 2020), Malaysia (Purwandari et al, 2022), Spain (Ceylan, 2020;Zeroual et al, 2020), Brazil (De Oliveira, et al, 2021Dairi, 2021), İndia (Shastri et al, 2020;Arora et al, 2020;Tandon et al, 2020), Nigeria (Abdulmajeed et al, 2020), France (Zeroual et al, 2020;Ceylan, 2020;Dairi, 2021), Canada (Chimmula & Zhang, 2020), South Korea (Pontoh et al, 2020;Dehesh et al, 2020), China (Dehesh et al, 2020;Zeroual et al, 2020), Iran (Dehesh et al, 2020;Talkhi et al, 2021), Austuralia (Zeroual et al, 2020), Russia (Dairi, 2021), Pakistan (Ali et al, 2020) etc. many studies with COVID-19 time series were conducted for many countries.…”
Section: Related Work and Backgroundmentioning
confidence: 97%
See 2 more Smart Citations
“…Within the scope of this study, many studies have been carried out in order to obtain predictions about the course of the pandemic through various time series models. In accordance with this purpose Turkey (Karcıoğlu et al, 2021;Akay & Akay, 2021;Fidan & Yuksel, 2022), Greece (Katris, 2021), Portugal (De Oliveira, et al, 2021, Italia (Ding et al, 2020;Ceylan, 2020;Dehesh et al, 2020), Worldwide (Sevli & Gülsoy;, Maleki et al, 2020, Petropoulos et al, 2022, USA (De Oliveira, et al, 2021;Özen et al, 2021;Shastri et al, 2020;Zeroual et al, 2020), Malaysia (Purwandari et al, 2022), Spain (Ceylan, 2020;Zeroual et al, 2020), Brazil (De Oliveira, et al, 2021Dairi, 2021), İndia (Shastri et al, 2020;Arora et al, 2020;Tandon et al, 2020), Nigeria (Abdulmajeed et al, 2020), France (Zeroual et al, 2020;Ceylan, 2020;Dairi, 2021), Canada (Chimmula & Zhang, 2020), South Korea (Pontoh et al, 2020;Dehesh et al, 2020), China (Dehesh et al, 2020;Zeroual et al, 2020), Iran (Dehesh et al, 2020;Talkhi et al, 2021), Austuralia (Zeroual et al, 2020), Russia (Dairi, 2021), Pakistan (Ali et al, 2020) etc. many studies with COVID-19 time series were conducted for many countries.…”
Section: Related Work and Backgroundmentioning
confidence: 97%
“…While the scope of these studies mostly consisted of the daily number of positive cases (Kumar & Susan, 2020;Papastefanopoulos et al, 2020;Zeroual et al, 2020;Chimmula & Zhang, 2020;Arora et al, 2020;Ding et al, 2020;Karcıoğlu et al, 2021;Dairi, 2021;Sevli & Gülsoy, 2020;Özen et al, 2021;Tandon et al, 2020;Purwandari et al, 2022;Pontoh et al, 2020;De Oliveira, et al, 2021;Shastri et al, 2020;Talkhi et al, 2021, Petropoulos et al, 2022, which is also the subject of this study, the authors also took into account the daily number of deaths (Karcıoğlu et al, 2021;Sevli & Gülsoy, 2020;Purwandari et al, 2022;Petropoulos et al, 2022, Pontoh et al, 2020Shastri et al, 2020;Talkhi et al, 2021) and the daily recoveries (Karcıoğlu et al, 2021;Sevli & Gülsoy, 2020;Purwandari et al, 2022;Purwandari et al, 2022;Pontoh et al, 2020;Zeroual et al, 2020;Dairi, 2021). In addition, many statistical and machine learning based time series models such as ARIMA (Ali et al, 2020;Tandon et al, 2020;Karcıoğlu et al, 2021;Ding et al, 2020;Özen et al, 2021;Abdulmajeed et al, 2020;Ceylan, 2020;Dehesh et al, 2020;<...…”
Section: Related Work and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found some underestimation and overestimation of the daily cases. [5,17,21,23] The authors applied deep learning methods, these methods can understand trends, dependencies, and structures.…”
Section: Literature Review On Modelling and Forcasting Covid-19mentioning
confidence: 99%
“…The total confirmed cases are predicted using the number of recovery patients. Purwandari et al [33] forecasted COVID-19 cases using the MLP, Neural Network Autoregressive (NNA), and Extreme Learning Machine (ELM). All methods achieved less than 12% MAPE for the days forecast.…”
Section: Introduction Covid-19 Is On the Public Health Emergency Ofmentioning
confidence: 99%